A mission concept for the low-cost large-scale exploration and characterisation of near earth objects. Issue 11 (1st June 2021) - Walker, Lewis; Di Carlo, Marilena; Greco, Cristian; Vasile, Massimiliano; Warden, Matthew
Abstract: This paper presents the preliminary mission and science analysis of a new mission concept for the large scale, low-cost exploration of Near Earth Objects (NEOs). The concept is to enable close range observations of NEOs by performing close flybys of a series of NEOs at one of their nodal points, with pairs of small spacecraft flying in formation. The paper presents a preliminary assessment of accessible asteroids and multi-target tour trajectories from data available in the JPL small-body database. The main instruments on board each spacecraft are a camera and a LIDAR which together can be used for orbit determination, surface imaging, direct asteroid ranging and asteroid mass estimation via intersatellite ranging. The paper provides a qualitative and quantitative assessment of the measurable quantities during each flyby. In particular, the feasibility of a novel method of NEO mass estimation is assessed.